Encapsulation of cancer therapeutic agent dacarbazine using nanostructured lipid carrier - Almoussalam, Musallam; Zhu, Huijun (JOVE, 2016)
The only formula of dacarbazine (Dac) in clinical use is intravenous infusion, presenting a poor therapeutic profile due to the low dispersity of the drug in aqueous solution To overcome this, a nanostructured lipid carrier (NLC) consisting of glyceryl palmitostearate and isopropyl myristate was developed to encapsulate Dac. NLCs with controlled size were achieved using high shear dispersion (HSD) following solidification of oil-in-water emulsion. The synthesis parameters, including surfactant concentration, the speed and time of HSD were optimized to achieve the smallest NLC with size, polydispersion index and zeta potential of 155 ± 10 nm, 0.2 ± 0.01, and -43.4 ± 2 mV, respectively. The optimal parameters were also employed for Dac-loaded NLC preparation. The resultant NLC loaded with Dac possessed size, polydispersion index and zeta potential of 190 ± 10 nm, 0.2 ± 0.01, and -43.5 ± 1.2 mV, respectively. The drug encapsulation efficiency and drug loading reached 98% and 14%, respectively. This is the first report on encapsulation of Dac using NLC, implying that NLC could be a new potential candidate as drug carrier to improve the therapeutic profile of Dac.
Keywords: Nanostructured lipid carrier; NLC; Dacarbazine; DAC; High shear dispersion; HSD; Drug delivery